2015
DOI: 10.1177/0194599815591809
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter Evaluation of the Effectiveness of Systemic Propranolol in the Treatment of Airway Hemangiomas

Abstract: This multisite study of AIH treatment with propranolol demonstrates similar effectiveness to surgical treatment modalities. Propranolol therapy for AIH had no complications, had potentially lower resource utilization, and should be considered a first-line AIH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Although 2 mg/kg/d is the most common starting dose, increasing the dose to 3 mg/kg/d resolved the majority of continued symptoms and rebound growth. In addition, other recent investigations support the use of higher starting doses without a reported increase in frequency of adverse effects . There was no significant difference in initial success rates when comparing 3 mg/kg/d to the lower doses.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Although 2 mg/kg/d is the most common starting dose, increasing the dose to 3 mg/kg/d resolved the majority of continued symptoms and rebound growth. In addition, other recent investigations support the use of higher starting doses without a reported increase in frequency of adverse effects . There was no significant difference in initial success rates when comparing 3 mg/kg/d to the lower doses.…”
Section: Discussionmentioning
confidence: 64%
“…Many case reports did not follow the patient to completion of their course of propranolol. The mean length of treatment documented in Elluru et al (15 months) is likely a more accurate representation of current practices, as their study only included cases with long‐term follow‐up through the termination of propranolol . Although this study did not identify rebound growth, it reported 22% of the 27 patients required additional medical or surgical intervention, with only one being a complete nonresponder to propranolol therapy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5 The efficacy of propranolol is striking, with the elimination of stridor within 24 h of initiation of therapy being seen in 85% of infants in one study. 6 Propranolol is given generally at a dose of 3 mg/kg/day. 7 Adverse incidents reported include bradycardia, hypotension, bronchospasm and hypoglycaemia.…”
Section: Key Pointsmentioning
confidence: 99%